The basic procedure with these problems is to solve one equation for one variable, substitute that into the second equation, solve for the second variable, substitute that into the first equation, and solve for the first variable.
Since the second equation has a lone y in it, I think I'd start by solving it for y -- y = 2x-9. Put that in the first equation and solve:
3x + 2*(2x-9) = 17
3x + 4x - 18 = 17
7x - 18 = 17
7x = 35
x = 5
Now that you know x, put it in the second equation and solve for y.
2*(5) - y = 9
10 - y = 9
10 = 9 + y
10 - 9 = y
y = 1
So the answer should be x=5, y=1. Adding or subtracting the two equations together can work, too, and is sometimes easier in certain cases. But at least when I was taught, this was the standard procedure used. I hope this helps.
2007-05-21 15:51:08
·
answer #1
·
answered by Dronak 2
·
0⤊
1⤋
3x+2y=17- (1) 2x-y=9 - (2) Multiply 2nd equation by 2 and add it to the first. (1) - 3x+2y=17 (2) - 4x-2y =18 7x = 35 x = 5 Substitute x value into second and solve for y ( 2)- 2*5 - y = 9 -y = -1 y = 1
2016-03-19 09:45:07
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
This Site Might Help You.
RE:
solve the system of equations 3x+2y=17, 2x-y=9?
2015-08-08 09:15:58
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
3x +2y =17 --(1)
2x-y =9 --(2)
From equation2, make y the subject
y=2x -9 --(3)
Substitute equation 3 into equation1,
3x +2(2x-9) = 17
3x +4x-18 =17
7x = 35
x = 5
SInce x=5,
y=2(5)-9 =1
2007-05-21 15:51:48
·
answer #4
·
answered by Trina C 2
·
1⤊
1⤋
First re-distribute 2x-y = 9 to y=2x -9
substitute for y 3x + 2(2x -9) = 17 , solve 3x + 4x -18 =17 or
7x =35 hence x = 5
Plug in y =2(5) - 9 , therefor y =1
Check 3(5) + 2(1) = 17 Solution is x= 5 , y = 1
2007-05-21 15:55:39
·
answer #5
·
answered by yflyfish 1
·
0⤊
2⤋
I love simultaneous equations
Lets do this one by the elimination method
3x + 2y = 17 (that's your first one)
4x - 2y = 18 (that's your second one - I've multiplied it all by 2)
add them together (cos if the LHS = RHS then you can add them)
7x + 0y = 35
7x = 35
Solve for x
Put that back into one of the equations
Like ... 2x - y = 9
So y = 2x - 9
You know what x is.
Solve for y
Give your answer to the teacher!
2007-05-21 15:48:22
·
answer #6
·
answered by Orinoco 7
·
1⤊
1⤋
2x - y = 9
-y = - 2x + 9
y = 2x - 9 then substitute
3x + 2(2x - 9) = 17
3x + 4x - 18 = 17
7x = 35
x = 5 now u have value of x, then substitute in for x
2x - y = 9
2(5) - y = 9
10 - y = 9
1 = y
ok , good luck
2007-05-21 15:59:09
·
answer #7
·
answered by VU H 1
·
1⤊
1⤋
For the best answers, search on this site https://shorturl.im/QtF4y
Isolate "x" or "y" in either equation. Let's isolate "x" in the 1st equation. First: subtract 2y from both sides (when you move a term to the opposite side, always use the opposite sign). 3x+2y-2y = 17-2y 3x = 17-2y (divide each term by 3). 3x/3 = 17/3 - 2y/3 x = 17/3 - 2y/3 Sec: substitute 17/3 -2y/3 with "x" in the 2nd equation. 2(17/3 - 2y/3) - 1y = 9 34/3 - 4y/3 - 1y = 9 34/3 - 7/3y = 9 (subtract 34/3 from both sides). 34/3 -34/3 - 7y/3 = 9-34/3 -7y/3 = -7/3 (multiply both sides by -3/7). (-3/7)(-7y/3) = (-3/7)(-7/3) y = 21/21 y = 1 Third: substitute 1 with "y" in the 1st equation. 3x+2(1) = 17 3x+2 = 17 (subtract 2 from both sides). 3x+2-2 = 17-2 3x = 15 (divide both sides by 3). 3x/3 = 15/3 x = 5 Solutions set: (5, 1)
2016-04-01 10:53:04
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
3x+2y=17(1st ) , 2x-y=9(2nd)
(multiply the 2nd equation with 2)
2(2x-y=9) =>4x-2y=18(3rd)
now add 1st & 3rd equation
3x+2y=17
4x -2y=18
=>7x=35(2y-2y gets cancelled)
=>x=35/7
=>x=5
therefore x =5
now substitute value of x in 2nd equation to get the value of y
2x-y=9
2(5)-y=9
10-y=9
y=1
2007-05-21 16:06:47
·
answer #9
·
answered by ASHWIN_525 s 2
·
1⤊
1⤋
y=2x-9
3x + 2(2x-9)=17
3x+4x-18=17
7x=35
x=5
y=2(5)-9
y=1
(5,1) mean x=5 and y=1
2007-05-21 15:51:39
·
answer #10
·
answered by AceDaMace 2
·
1⤊
1⤋